Ozone position paper : final version: prepared by the Ad hoc Working Group on Ozone Directive and Reduction Strategy Development (Document, 1999)
This position paper is a background document to help the Commission prepare its proposal for the new directive on ozone in ambient air (one of the "daughter directives" required by the Council Directive on the Assessment and Management of Ambient Air Quality - the "Framework Directive"). The new ozone directive will replace the current Council Directive 92/72/EEC on air pollution by ozone. The proposal for the new directive will form part of an integrated package proposing the EU strategy on accidification, eutrophication and ozone.